PROXIMATE, PHYTOCHEMICAL, MINERAL COMPOSITION AND ANTIOXIDANT EFFECTS OF METHANOL EXTRACT OF Persea americana (Avacado pear) SEED (FUDMA JOURNAL OF SCIENCES, 2024)
The proximate, phytochemical, mineral, and antioxidant composition of Persea americana seed methanol extract was examined in this work. Standard procedures were used for both proximate, mineral composition and quantitative evaluations. Lipid peroxidation, reducing power, and 2,2-diphenyl-1-picryhydrazyl tests were used to measure the antioxidant activity. Using absorption spectroscopy techniques, antioxidant vitamins A, E, and C as well as enzymes (superoxide dismutase, peroxidase, and catalase) were evaluated. Based on the proximate analysis, the P. americana seeds have higher levels of protein (21.00 ± 0.88 %), fat (25.73 ± 2.01 %), and carbohydrates (32.05 ± 1.21 %), but they have lower levels of moisture (8.98±0.10 %) and ash (3.28±0.16 %). A quantitative phytochemical study found that there were phenols (3.51±0.42 mg/100 g),saponins (0.05±0.38 mg/100 g), alkaloid (0.70±0.37mg/100 g), beta-carotene (32.24±0.55mg/100 g), lycopene (6.84±0.52 mg/100 g), flavonoids (34.14±3.13 mg/100 g), phytate (0.00±0.03 mg/100 g), cardiac glycosides (0.37±0.01 %), total phytosterol (21.25±0.12 mg/100 g), stigmasterol (13.16±0.15 mg/100 g) and campesterol (6.16±0.12 mg/100 g). The mineral composition showed that iron and manganese had the lowest quantities, while potassium, calcium, and magnesium had the highest concentrations. The analyzed samples' potential therapeutic benefits in phytomedicine may be attributed to their respective chemical compositions. Out of all the antioxidant vitamins tested, vitamin E had the highest amount (267.73 ± 0.07 mg/100g), followed by vitamin A (7.60 ± 0.01 mg/100 g) and vitamin C (3.88 ± 0.03 mg/100 g). As extract concentration increased, there was a substantial (p
Keywords: Persea americana seeds; Phytochemical composition; Proximate; Minerals; Antioxidant enzymes; Vitamins